Understanding criminal behaviour : psychosocial perspectives on criminality and violence - Jones, David W. (David Wyn), 1964-
"This book offers a concise and accessible introduction to criminal behaviour, examining and integrating perspectives from criminology and psychology. It explores a range of 'psychosocial' approaches that seek to understand the emotions that surround criminal behaviour, allowing for an exploration of individual differences and social and culture issues which help to bridge the gap between disciplinary approaches"--